Prevalence of knowledge and use of the female condom in South Africa - Guerra, Fiona M.; Simbayi, Leickness C. (© 2014 © Springer Science+Business Media New York, 2017)
This article was published in AIDS and Behavior [© 2014 Springer Science+Business Media New York] and the definite version is available at: http://link.springer.com/article/10.1007/s10461-013-0580-3